Enhancing access to learning aids and resources at windhoek correctional facility - N Sisinyize; G Tubaundule; M Kaunozondunge; A Kambimbi; D Mujoro G (Papanda Publisher, 2023)
This research study aims to improve access to learning aids and resources for inmates in Technical, Vocational Education and Training (TVET) within the confines of the Windhoek Correctional Facility, aiming to facilitate the rehabilitation and successful reintegration of incarcerated individuals, as well as suggest possible recommendations to achieve enhanced access to learning Aids and Resources at correctional facilities in Namibia. The study used a qualitative-method approach, including case study, interviews, and observations, to evaluate the facility's existing learning environments and assess the sufficiency and accessibility of resources. It also explores the impact of restricted access on inmates' educational and personal growth. The research seeks inspiration from successful models in other correctional facilities and identifies innovative approaches, such as technology integration, partnerships with educational institutions, and community involvement. The findings will inform policy recommendations and practical interventions.